Cheiloscopy and blood groups: Aid in forensic identification - Bushra Karim; Devanand Gupta (Saudi Dental Journal)
Introduction: Every person has certain features that make them radically distinct from others. One such feature is lip prints. Lip prints remain the same throughout life and are uninfluenced by injuries, diseases, or environmental changes. Different individuals have specific blood groups according to the various antigen–antibody reactions in their bloodstream. Aim: To determine the distribution of different patterns of lip prints among subjects having different ABO and Rh blood groups. Objective: To determine the correlation between respective characteristics of subjects. Methodology: In this study, lip prints were obtained from 122 subjects (62 males and 60 females), and associated blood-group matching was performed to determine the predominant lip print type and to determine any correlation between lip print types and blood groups. Tsuchihashi’s classification of type I (complete vertical grooves), type I′ (incomplete vertical grooves), type II (forking grooves), type III (intersecting grooves), type IV (reticular grooves), and type V (indeterminate grooves) was used to compare with the ABO and Rh blood grouping systems. Result: No correlation was found between lip prints and blood groups. Conclusion: No significant correlation exists between blood group and lip prints. Lip prints play a vital role in identification because they are unique. Keywords: Forensic odontology, Cheiloscopy, Blood groups